UPPER AND LOWER BOUNDS OF THE BASIS NUMBER OF KRONECKER PRODUCT OF A WHEEL WITH A PATH AND A CYCLE - Ayhan Khalil; Ghassan T. Marougi (College of Education for Pure Sciences, 2007)
ABSTRACT The basis number, b(G) ,of a graph G is defined to be the smallest positive integer k such that G has a k-fold basis for its cycle space. We investigate upper and lower bounds of the basis number of Kronecker product of a wheel with a path and a cycle. It is proved that and , and , , .